Enhancing Healthcare Imaging Security: Color Secret Sharing Protocol for the Secure Transmission of Medical Images - Suresh Sankaranarayanan; Prema Bhushan Sahane; Maheshwari Divate; A. John Blesswin; G. Selva Mary; A. Catherine Esther Karunya; Pascal Lorenz (IEEE Access, 2024)
Healthcare has seen extensive use of internet technology for the transmission of electronic healthcare records among healthcare professionals and patients for diagnosis and treatment. Now with the advent of digital and internet technology, multimedia data also be transmitted in the form of images, and videos which include X-rays, Computed Tomography (CT), Magnetic Resonance Imaging (MRI), and so forth. It is direly important to secure these medical images which are transmitted digitally among healthcare professionals and patients. Visual Cryptography (VC) comes as a solution for encrypting and securing these multimedia data for transmission. The process of VC involves dividing the original Secret Color Image into Shares and distributing them to the intended recipients. These shares are then combined, either physically or digitally, at the receiving end to reveal the original multimedia content. VC faces three main challenges which are the quality of reconstructed images, pixel expansion, and computational complexity. So, we in research developed a novel approach called Color Secret Sharing Protocol (CSSP) for the secure transmission of individual secret images within multimedia systems. The newly proposed protocol which is CSSP is been validated on sample medical images using MATLAB where the reconstructed image quality is improved by up to 1.345% compared to other existing methods. CSSP enhances multimedia security by utilizing cover images and simultaneously reducing complexity, effectively addressing pixel expansion within the context of multimedia transmission.